Developing Intercultural Communicative Competence through Arabic Film-Based Translation Learning in Islamic Boarding School - Al Akcbar Mastur; Hasan Saefuloh; Robby Jundi Lestari; Vieka Tauhidah Nafisendy (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2026)
Nuqayah Islamic Boarding School (Pesantren) in Guluk-Guluk, Sumenep, Madura, utilizes Arabic films to support Arabic language learning. However, students often encounter difficulties in translating cultural expressions in film dialogues, including idioms, dialects, contextual meanings, and sociocultural nuances. This study aims to explore Arabic film-based translation (tarjamah) learning, focusing on teachers’ instructional strategies, students’ challenges, and pedagogical efforts to address these difficulties. A qualitative case study design was employed. Data were collected through non-participant observation, semi-structured interviews, and documentation involving 30 students and 5 Arabic language teachers. Data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings indicate that teachers employed repeated viewing, textual support, cultural discussions, and communicative oral translation practices. Students’ challenges extended beyond linguistic issues to include difficulties in interpreting cultural symbols, nonverbal communication, and social contexts represented in Arabic films. The pesantren environment further supported language retention and cultural internalization through the daily use of Arabic. This study concludes that Arabic film-based translation pedagogy contributes to the development of students’ intercultural communicative competence by integrating language learning, cultural interpretation, and contextual communication.